Interrelation of urban farming and urbanization: an alternative solution to urban food and environmental problems due to urbanization in Indonesia - Giyarsih, Sri Rum; Armansyah,; Zaelany, Andy Ahmad; Latifa, Ade; Setiawan, Bayu; Saputra, Dani; Haqi, Muamar; Lamijo,; Fathurohman, Apit (Frontiers in Built Environment, 2024)
Urbanization is the process of increasing the population migrating to urban areas, and urban farming is a farming practice carried out within the city. Both concepts have significant impacts on urban life and the environment. This research aims to analyze the interrelation of the positive impacts of urban farming and the negative impacts of urbanization. The analysis focuses on food and environmental aspects as alternative problem-solving methods in the cities of Bandung, Denpasar, and Palembang. This research uses qualitative method. Data collection uses field interview techniques with 30 informants, as well as a review of several scientific articles, previous research results, and reports from data-providing agencies such as the Indonesian Central Bureau of Statistics. Data analysis used the Miles and Huberman Model, with the stages of reduction, display, and conclusion drawing. The results of the analysis show that there is an interrelation between the positive impacts of urban farming and the negative impacts of urbanization in the cities of Bandung, Denpasar, and Palembang. In terms of food aspect, urban farming can provide various types of easily accessible food for urban dwellers, such as vegetables, fruits, fisheries, and small-scale livestock. The food produced is relatively close to residential areas, so the quality is still fresh and healthy and the price is affordable as well. In the environmental aspect, urban farming can optimize the use of limited or vacant land in residential areas into productive land, such as for green spaces, farming activities, gardening, fisheries, and livestock. Other functions include enhancing the beauty of the environment, reducing household waste, and preserving organism biodiversity.